Hepatic artery aneurysm with no proximal neck and proper hepatic artery bifurcation involvement - Mellucci Filho, Pedro Luciano [UNESP]; de Marqui, Bruno Aparecido Lourenço; Isper, Letícia; Pugas, Adrielle Andrade; Martelli, César Alberto Talavera; Melo, Rodolfo Dahlem; Bertanha, Matheus [UNESP]; Sobreira, Marcone Lima [UNESP] (FapUNIFESP (SciELO), 2024)
We report the case of a patient with a saccular aneurysm of the hepatic artery with maximum diameter of 2.8 cm, no proximal neck, and involving the bifurcation of the proper hepatic artery, constituting a hostile anatomy for endovascular treatment, which would usually be the first choice for such cases. We performed open surgical treatment with resection and reconstruction using an autologous graft (internal saphenous vein). We illustrate the surgical technique used for adequate vascular exposure of the celiac trunk and hepatic hilum (which is often an area little explored by vascular surgeons) and of structures anatomically close to the hepatic artery. We also illustrate the anastomosis with telescoping technique. We demonstrate the need for vascular surgeons to master the anatomy and classical surgical technique for visceral branches, even in the era of minimally invasive procedures.
Aneurisma de artéria hepática sem colo proximal e acometendo bifurcação de artéria hepática própria
Keywords: aneurysm; hepatic artery; hepatic circulation; vascular surgery